Effect of cardiac resynchronization therapy on left ventricular fibrosis-related mRNA expression profile in patients with end-stage heart failure. (25th November 2020) - Sayour, A.A; Olah, A; Ruppert, M; Barta, B.A; Polos, M; Benke, K; Hartyanszky, I; Szenthe, K; Banati, F; Szathmary, S; Merkely, B; Radovits, T
Abstract: Background: When indicated, cardiac resynchronization therapy (biventricular pacing, CRT) decreases mortality in patients with heart failure (HF) and reduced ejection fraction, especially in those with non-ischemic cardiomyopathy. This is reflected by relatively rapid improvement of left ventricular (LV) end-diastolic diameter (LVEDD) and LV ejection fraction (LVEF) indicating reverse remodelling. These LV structural and functional improvements are accompanied by characteristic changes in LV gene expression profile. However, whether beneficial gene expression alterations related to biventricular pacing are sustained independently of structural and functional reverse remodelling is unclear. Purpose: We aimed to compare LV fibrosis-related mRNA expression profile in end-stage HF patients with idiopathic dilated cardiomyopathy (DCM) who were not on CRT versus to those on CRT. Methods: Left ventricular myocardial samples were harvested from end-stage HF patients undergoing heart transplantation (HTX). Inclusion criteria were negative family history of DCM, negative coronarography (i.e. non-ischemic), no relevant comorbidity (e.g. diabetes, hypertension) and no history of myocarditis. Accordingly, the following patient groups were included: 1.) DCM (n=12, 17% female, mean age [±standard deviation] 46.8±11.8 years) without CRT and 2.) CRT-DCM (n=12, 42% female, mean age 47.8±12.3 years) which comprised DCM patients on active CRT for mean 3.2±2.4 years until HTX. LV RNA was extracted and subjected to a commercially available mRNA expression panel interrogating 760 genes related to the development and regulation of fibrosis. Normalization to 10 housekeeping genes and batch corrections were conducted as per protocol. LV mRNA expression of atrial-natriuretic peptide (ANP) was quantified using qRT-PCR. Results: Markers of reverse remodelling including LVEDD (73.4±8.3 mm vs 75.4±9.9 mm), LVEF (21.9±3.7% vs 18.5±6.8%) and LV ANP mRNA expression (arbitrary units: 1.05±1.80 vs 1.04±0.88) were comparable between DCM and CRT-DCM patients (all P>0.05), respectively. High-throughput mRNA expression screening revealed significant (all P<0.001) downregulation of 3 genes proven to be implicated in adverse LV remodelling: alpha catalytic subunit of protein phosphatase 2 (PPP2CA), interleukin 20 receptor subunit beta (IL20RB) and lipoprotein lipase (LPL). According to pathway analysis using directed significance scores, CRT was associated with collective upregulation of genes modifying complement activation (SERPING1, C1S, CFH) and collective downregulation of genes promoting cell proliferation (PPP2CA, ANAPC7, HSP90AA1, CSNK2B). Conclusions: Independently of structural and functional reverse remodelling, CRT might be associated with slightly favourable LV expression profile of genes related to the regulation and development of fibrosis. This suggests that biventricular pacing might be beneficial on the molecular level beyond improvement of LV structure and function. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Fund of Hungary, Higher Education Institutional Excellence Programme of the Ministry of Human Capacities of Hungary